2004
DOI: 10.1191/1352458504ms1079sr
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous corticosteroids in the postpartum period for reduction of acute exacerbations in multiple sclerosis

Abstract: In order to assess the effectiveness of monthly intravenous corticosteroids in reducing childbirth-associated acute exacerbations in multiple sclerosis (MS), we compared pregnant patients followed up in our MS clinic. During the first period (1996-1998), 22 patients did not receive any treatment after delivery. During the second period (1999-2001), following the publication of the PRIMS study, 20 patients were treated monthly with 1 g of intravenous corticosteroids during the six months of the postpartum perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 4 publications
1
36
1
3
Order By: Relevance
“…12 Another study had already shown a beneficial effect of postpartum IV steroids in relapse rate reduction in a small group, but with monthly infusion for 6 months. 13 In our study we found a significant reduction in the percentage of patients having relapses during the first postpartum trimester in those who received postpartum IV steroids compared with those who did not receive them. The difference between the two groups in the percentage of patients having relapses was not significant during the second and third postpartum trimesters.…”
Section: Resultssupporting
confidence: 55%
“…12 Another study had already shown a beneficial effect of postpartum IV steroids in relapse rate reduction in a small group, but with monthly infusion for 6 months. 13 In our study we found a significant reduction in the percentage of patients having relapses during the first postpartum trimester in those who received postpartum IV steroids compared with those who did not receive them. The difference between the two groups in the percentage of patients having relapses was not significant during the second and third postpartum trimesters.…”
Section: Resultssupporting
confidence: 55%
“…As noted earlier, ideally this issue is dealt with before pregnancy occurs. Small-scale studies have evaluated postpartum prophylactic intravenous immune globulin, as well as pulse corticosteroids, to minimize relapses with reported success [De Seze et al 2004;Haas and Hommes, 2007]. Hormonal therapy (percutaneous 17-β estradiol 100 µg weekly along with oral nomegestrol acetate 10 mg daily) was evaluated in the POPARTMUS trial, but showed no ability to suppress postpartum relapses or MRI activity [Durand-Dubief et al 2014].…”
Section: Disease Activitymentioning
confidence: 99%
“…Little is known about potent postpartal relapse prevention. Prophylactic application of intravenous steroids showed some effect in a small cohort [de Seze et al 2004], but this may interact with wound healing after delivery. A contraindication exists for the current available disease-modifying therapies (DMTs; i.e., interferon (IFN) beta or glatiramer acetate) during pregnancy and breast-feeding [Hoffmann et al 2006;Coyle et al 2004].…”
Section: Introductionmentioning
confidence: 99%